15.
[tex]\sqrt{11\frac{1}{4} \cdot20} - \sqrt{25.6 : 10} = \sqrt{\frac{45}{4}\cdot 20 } - \sqrt{2.56} = \sqrt{45\cdot5} - 1.6 = \sqrt{225} - 1.6 = 15 - 1.6 = 13.4[/tex]
16.
[tex]\sqrt[3]{(\sqrt[3]{3} )^{3}+(\sqrt[3]{6} )^{3}+(\sqrt[3]{7})^{3} } = \sqrt[3]{3+6+7} = \sqrt[3]{16}[/tex]
Jest 2 razy mniejsza, bo [tex]\sqrt[3]{128} : \sqrt[3]{16} = \sqrt[3]{128 : 16} = \sqrt[3]{8} =2[/tex]
17.
[tex]a = \sqrt[3]{\frac{1}{64} } = \frac{1}{4}=0.25[/tex]
[tex]b= \sqrt{1.44} = 1.2[/tex]
[tex]c = \sqrt[3]{0.008} = 0.2[/tex]
[tex]d = \sqrt{\frac{25}{16} } = \frac{5}{4} = 1.25[/tex]
[tex]e = \sqrt{0.49} = 0.7[/tex]
d > b > e > a > c